EVALUATION AND ANALYSIS OF GOLF GAME AND PORTUGUESE COURSES (Fiep Bulletin - online, 2014)
The purpose of this study was to characterize the golfers and the golf-courses in Portugal. It was based on the gathering of facts made in 2006.This gathering consisted in the answering of two inquiries-one directed to the socio-economic characterization and the other to the nourishment profile of the golfers-as well as in observation and direct measurement of the golf-courses and the golfers. The golfers were evaluated just before the competition and the follow items were determined: weight, stature, building, 4 skin folds (bicipital, tricipital, subscapular, supraspinal), in accordance with the proposed method. The values of the bio impedance were also measured and cardio-frequenceometres applied during the round. The sample was built out of 327 golfers, 46 being females. The athletes were aged between 50 and 82 years old and body weight between 75 and 90 Kilos Forty-three golf-courses were analized in detail;8 in Porto and north of Portugal,2 in Beiras, 14 in Lisbon, 1 in Alentejo and 18 in Algarve; in what concerns the nationality of the golfers, and the characteristics of the effort caused by one round as well as the mobility of the golfers at the golf-courses. We have resorted to the SPSS statistics program, version 11,5 to treat the facts. We carried out the describing statistics and tests of variation analysis. We also made the factorial analysis.
Keywords: Golf; Golfers; Old age